Framing Justice and Public Perception: A Discourse Analysis of the Agus Salim Donation Controversy in Online Media - Inti Englishtina; Steffie Mega Mahardhika; Kristin Marwinda (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This study explores the discourse surrounding the Agus Salim donation controversy, focusing on how media narratives and legal rhetoric shape public perception. Drawing on two primary sources—articles from Brilio.net and KapanLagi.com—the research employs critical discourse analysis to examine the framing of key events, including allegations of donation mismanagement, legal strategies, and the public's reaction to the case. The findings reveal how media outlets construct competing narratives, emphasizing the roles of public figures, lawyers, and victims in influencing the discourse. By analyzing language use, power dynamics, and ideological positioning, this study highlights the interplay between legal rhetoric and public opinion in cases of social and moral significance. The research contributes to understanding how controversies are framed in digital media and their implications for justice and accountability in contemporary society.